Peningkatan Literasi Keuangan dan Kompetensi Akuntansi Dasar Pada Kelompok Tani Kampung Waibron - KP Kambuaya, Maylen; M. Tandililing, Elia; Rofingatun, Siti; Sesa, Pascalina V.S. (UNIVERSITAS CENDERAWASIH, 2025)
This community service activity aims to provide financial education and enhance basic accounting competencies through two forms of mentoring: calculating Cost of Goods Sold (COGS) and recording simple cash flows for the Farmer Group in Waibron Village, West Sentani District. Through a participatory approach, the program encourages the Farmer Group to be able to calculate production costs incurred, determine selling prices, and record business income and expenses sustainably. The methods used in this activity include observation, interviews, socialization, and hands-on practice in calculating COGS and recording cash flows. With the implementation of this mentoring program, the Farmer Group in Waibron Village is expected to improve their understanding and competencies in managing their business sustainably, foster awareness of organizing their business from an early stage, and support the creation of sustainable economic cycles among farmers. Keywords: Accounting, Cost of Goods Sold, Cash flows